Current-mode multiphase sinusoidal oscillator using current differencing transconductance amplifiers - Tangsrirat, Worapong; Tanjaroen, Wason (My University, 2008)
This paper describes a simple current-controlled current-mode multiphase sinusoidal oscillator based on current differencing transconductance amplifiers (CDTAs) as active components. The proposed oscillator circuit, which employs only one CDTA and one grounded capacitor for each phase, can generate arbitrary n current-output signals (n being even or odd) equally spaced in phase, all at high output impedance terminals. The oscillation condition and the oscillation frequency can be controlled electronically and independently through the bias current of the CDTA. The oscillator has low-component count, low-sensitivity performance, and is highly suitable for monolithic implementation. PSPICE simulation results are given to confirm the operation of the proposed oscillator. © Birkhäuser Boston 2007.
Keywords: CDTA; Current-modecircuit; Multiphase sinusoidal oscillator (MSO)